Carbon encapsulated iron oxide for simultaneous Fenton degradation and adsorption of cationic and anionic dyes from water. Issue 6 (December 2022) - Haris, Muhammad; Zavabeti, Ali; Khan, Muhammad Waqas; Murdoch, Billy J.; Paz-Ferreiro, Jorge; Mahmood, Nasir; Eshtiaghi, Nicky
Abstract: Adsorption and Fenton oxidation processes are considered the most effective ways to treat industrial dye effluent. However, the separation of adsorbent materials and the leaching of secondary pollutants are big hurdles. To resolve these issues, here, we have developed a unique hybrid structure (Fe3 O4 @C) by encapsulating iron oxide into carbon shells using olive mill waste in a one-step process. The resulting unique core-shell Fe3 O4 @C structure possessed both tunned surface functional groups (carboxylic, carbonyl, and amines) and magnetic properties, which can be easily separated from treated water using a magnet. Upon using Fe3 O4 @C as a catalyst, it simultaneously removed/ degraded both Congo red (CR) and methylene blue (MB) up to 94% through Fenton oxidation. ICP-MS analysis detected negligible (6.6 ppb) iron leaching even in Fenton degradation, which is far lower than the allowable leaching limit of 300 ppb showing the efficacy of the developed structure. This is due to the core-shell structure where Fe3 O4 remains active inside the core due to dual protection by encapsulating inside a semicrystalline carbon shell, which is then protected by a porous carbon matrix. This double protection assists high adsorption and maintains efficient charge transfer that favors high catalytic activity with limited iron leaching. Further to prove this Fe3 O4 @C was used in 5 consecutive adsorption cycles, where it removed 94.4% MB after 5th cycle and even preserved the pristine core-shell structure and chemical bonds as indicated by ex-situ Energy-dispersive X-ray spectroscopy, High-angle annular dark field, High-angle annular bright field, and X-ray photoelectron spectroscopy analysis. Hence, this study successfully showed that olive waste could be converted into a functional material that can further be used at a large scale for pollutant removal from wastewater. Graphical Abstract: ga1 Highlights: Carbon encapsulated iron oxide was developed through one-step hydrothermal process. Fe3 O4 @C has core-shell structure and can be separated by external magnet. Fe3 O4 @C simultaneously removed (∼100%) both cationic and anionic dyes. Fe3 O4 @C preserved its core-shell structure after adsorption. Negligible Fe leaching (6.6 ppb) after Fenton degradation depicting good stability.